Performance of the social worker in front of the autistic child and his family in the reference center of social assistance in a municipality in the interior of Maranhão (Research, Society and Development, 2023)
Autistic Spectrum Disorder (ASD) is a disorder that is intrinsically linked to the child's neurodevelopment. the present study had the general objective of understanding the performance of the Social Worker in relation to the person with ASD, and specific objectives: to point out the laws and projects directed at the person with ASD; know the specificities of ASD and point out the importance of family and Social Work for the social inclusion of people with ASD. It was decided to carry out a field and bibliographic research. It was possible to analyze, through a questionnaire carried out with a professional in the area, that work as a social worker is hard and that it constitutes a challenge to insert, train, develop and generate hope for families. The role of the family for people with the spectrum must be developed in more detail, as the pace is different and their integration into the social environment can take time, but on the other hand there must be playfulness, intimacy and other aspects, especially in the care process or rehabilitation in social institutions.